2005
DOI: 10.1002/humu.9389
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of PDCD10 mutations in a panel of CCM3 probands: potential for a fourth CCM locus

Abstract: Cerebral cavernous malformations (CCMs) are vascular abnormalities of the brain that can result in a variety of neurological disabilities, including stroke and seizures. Linkage analyses using autosomal dominant families manifesting CCMs have identified three different causative loci on chromosomes 7q21.2 (CCM1), 7p13 (CCM2), and 3q25.2-q27 (CCM3). Mutations in the gene Krit1 are responsible for CCM1, mutations in the gene MGC4607 are responsible for CCM2, and mutations in the gene PDCD10 were recently reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(63 citation statements)
references
References 14 publications
3
60
0
Order By: Relevance
“…Although both result in premature stop codons, the mutated genes encode proteins that are close in length to the wild-type protein (212 residues) (Fig. 9A) (Bergametti et al, 2005;Liquori et al, 2006). When we expressed these mutants, we found that their levels of expression were similar to that of wild-type CCM3 (Fig.…”
Section: Clinically Relevant Ccm3 Mutants Cannot Rescue the Ccm3 Deplmentioning
confidence: 89%
“…Although both result in premature stop codons, the mutated genes encode proteins that are close in length to the wild-type protein (212 residues) (Fig. 9A) (Bergametti et al, 2005;Liquori et al, 2006). When we expressed these mutants, we found that their levels of expression were similar to that of wild-type CCM3 (Fig.…”
Section: Clinically Relevant Ccm3 Mutants Cannot Rescue the Ccm3 Deplmentioning
confidence: 89%
“…CCM3 has been identified as a cause of familial CCM by positional cloning studies (6, 7), but human genetic studies have revealed that CCM3 mutations are a relatively rare cause of the disease (36,37), and forward genetic screens for cardiovascular mutants in zebrafish have failed to identify CCM3 as a regulator of cardiovascular development. Thus, whether CCM3 plays a central role in this vascular signaling pathway similar to those of CCM1 and CCM2 has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…PDCD10 is a functionally important gene, although mutations in PDCD10 are uncommon in CCM (Verlaan et al, 2005), and low frequency of PDCD10 mutations were identified in a panel of CCM3 probands (Liquori et al, 2006). CCMs are hamartomatous vascular malformations characterized by abnormally enlarged capillary cavities without intervening brain parenchyma.…”
Section: Discussionmentioning
confidence: 99%